Koekenttien maaperän epätasaisuudesta - Vuorinen, Jouko (Agricultural and Food Science, 1946)
The inequality of the Finnish soil with regard to the varying thickness of the soil layers of different age in heavy clay has previously (1) been described as a factor of strong influence on test conditions. The present paper deals chiefly with the effect of the acidity of the soil on the inequality of muddy clay and silt soil, and with the relation of the mechanical composition of silt soil and the various factors of fertility to the productivity of the test soil. The investigation leads to the following conclusions: 1. Even comparatively small changes in the mutual quantitative relations between the fine (<(0.06 mm) mineral refractions of the soil of the test field may have a decisive effect on the physical propercies of the soil and on the inequality of the test field. 2. Among the soil properties of an effectively cultivated, fertile test field in good condition the acidity may develop into a strongly yield restricting factor and thus give rise to quite considerable inequalities in the test field. 3. In the different parts of the test fields the quantities of exchangeable lime (2) also show consider able differences which may affect the yield, especially in the case of soils poor in lime. 4. Bearing in mind the results of the above investigation, it is advisable carefully to investigate the soil when choosing the sites for new experiment stations. Above all it should be ascertained that the experiment station will comprise the typical soils representing the different soils of the district. 5. At the same time special attention should be devoted to the investigation of the plots intended for test fields. In the first place the mechanical composition of the soil should be carefully determined and also at any rate the acidity of the soil and the exchangeable lime. 6. Plant growing tests as a method of investigation involve such an amount of work and expense and their results are so important to agriculture that a thorough soil investigation should be carried out on all test fields, this being the most important condition for the effectiveness and success of such tests.